Enhancing Computer Science: Exploring the Power of Decentralized Blockchain Techniques in IoT Security and Privacy - Chetan Papade, Sujata; Deshmukh, Suwarna; Pradyumna Bora, Neha; Kavin, R.; P. Deshpande, Prasanna; Mayee Adavala, Kiran; Yadav, Krishan Kant (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The rapid growth of the Internet of Things (IoT) has brought about numerous opportunities and challenges in terms of security and privacy. With the increasing number of interconnected devices, traditional centralized approaches to security have become inadequate, leaving IoT systems vulnerable to attacks. In recent years, decentralized blockchain techniques have emerged as a promising solution to address the security and privacy concerns of IoT. This review paper explores the power of decentralized blockchain techniques in enhancing computer science, focusing on their application in IoT security and privacy. The paper discusses the fundamental concepts of blockchain technology, its benefits, and its potential applications in IoT security. It also highlights the challenges and future research directions in this field. By harnessing the power of decentralized blockchain techniques, we can pave the way for a more secure and privacy preserving IoT ecosystem.